2010
DOI: 10.5817/soc2010-2-23
|View full text |Cite
|
Sign up to set email alerts
|

Nová sociální rizika a reformní trendy evropských sociálních států v reakci na ně

Abstract: The article presents a concept of new social risks developed by Esping-Andersen (1999), and Armingeon, Bonoli (2006) and general reform trends of welfare states in reaction on these risks. The first part of the study concerns development and reform trends in Western European countries. The second part focuses on specificity of new social risks and reform trends in Central and Eastern European countries. The article concludes that general trends of welfare state reforms in response to emerging social risks in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…In line with Klimplova's conclusion [11], our study has shown an subjectively risk of increase in the number of unemployed and the subjectively perceived risk of skills obsolescence, with the associated risk of maintaining adequate employment. Furthermore, our study found a subjectively risk of under-qualification, and an unwillingness to educate or train.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with Klimplova's conclusion [11], our study has shown an subjectively risk of increase in the number of unemployed and the subjectively perceived risk of skills obsolescence, with the associated risk of maintaining adequate employment. Furthermore, our study found a subjectively risk of under-qualification, and an unwillingness to educate or train.…”
Section: Discussionsupporting
confidence: 90%
“…Klimplová [11] examined new social risks in central and eastern European countries in the transition from centrally planned to market economies. These include a rise in the number of unemployed persons, a significant decline in the agricultural and industrial workforce, the formation of a new managerial elite (class), the abandonment of lifetime employment status (for more flexible employment contracts), a decline in fertility rates, an ageing population, fewer marriages, higher divorce rates, and increasing poverty among both single parents with children and households with multiple children.…”
Section: Introductionmentioning
confidence: 99%